Tinjauan Penerapan Konsep Pencahayaan Dengan Pendekatan Lapisan Cahaya Pada Desain Interior Kafe - Isdianto, Fadhil Achmadi (Program Studi Desain Interior Unikom, 2024)
Lighting in cafés is a factor that needs to be considered in creating a comfortable and attractive atmosphere for visitors. This study discusses lighting in café interior design using the theory of layered lighting or the